Evaluating occupational stress in manufacturing workers using a dot probe task game board: A pilot study. - Lee, Poh Foong; Chong, Kai Wen; Wong, Mei-Yi; Kok, Siak Wah (Work, 2026)
Background: Occupational stress in manufacturing negatively impacts worker health and productivity. Effective tools for assessing stress levels in this high-risk industry can support interventions aimed at improving worker well-being. Objective: This pilot study aims to develop and validate a dot probe task game board to measure occupational stress, integrating the Perceived Stress Scale (PSS-10), the Technology Acceptance Model (TAM), and EEG brainwave analysis. Methods: The dot probe task measured reaction times to stress-related stimuli, with EEG recordings (focused on the AF8 electrode) taken before and after the task. A RidgeCV regression model assessed predictive factors, emphasizing stress levels measured by the PSS-10. Results: Significant reaction time differences validated the task's sensitivity to stress-related cognitive impairment. The RidgeCV model achieved high predictive accuracy (R² = 0.945), identifying the PSS-10 as a primary predictor of stress. EEG data provided insights into stress-induced neurobiological changes in cognitive function. Conclusion: The study supports the integration of the dot probe task in occupational health assessments, highlighting its potential to improve well-being and inform targeted interventions in manufacturing and other high-risk sectors.